2010
DOI: 10.1155/2011/690346
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Upper Respiratory Tract Infections in Primary Care: A Randomized Study Using Aromatic Herbs

Abstract: This study is a prospective randomized double-blind controlled trial whose aim was to investigate the clinical effects of aromatic essential oils in patients with upper respiratory tract infections. The trial was conducted in six primary care clinics in northern Israel. A spray containing aromatic essential oils of five plants (Eucalyptus citriodora, Eucalyptus globulus, Mentha piperita, Origanum syriacum, and Rosmarinus officinalis) as applied 5 times a day for 3 days and compared with a placebo spray. The ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
53
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 26 publications
0
53
0
1
Order By: Relevance
“…In another prospective, randomized double-blind controlled trial, the activity of a spray containing EO of Eucalyptus citriodora, E. globulus, Mentha x piperita, Origanum syriacum, and Rosmarinus officinalis were studied in patients with URTI [36], 34 patients in the test group used this spray 5 times a day (4 spraying each time) for 3 days. Then the change of the most debilitating symptoms (sore throat, hoarseness or cough) was assessed in patients.…”
Section: Human Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…In another prospective, randomized double-blind controlled trial, the activity of a spray containing EO of Eucalyptus citriodora, E. globulus, Mentha x piperita, Origanum syriacum, and Rosmarinus officinalis were studied in patients with URTI [36], 34 patients in the test group used this spray 5 times a day (4 spraying each time) for 3 days. Then the change of the most debilitating symptoms (sore throat, hoarseness or cough) was assessed in patients.…”
Section: Human Trialsmentioning
confidence: 99%
“…There was no difference in symptom severity between the two groups after 3 days of treatment. Based on these results, authors suggested the local, rather than systemic effect of this spray on the upper respiratory tract [36]. In a multi-centre, randomized, double-blind, placebo-controlled clinical trial, the efficacy and tolerability of GeloMyrtol® (=Myrtol®) forte was studied in acute bronchitis [37], 413 patients were included and randomized, 202 participants received GeloMyrtol® 300 mg, 4 capsules per day for 2 weeks.…”
Section: Human Trialsmentioning
confidence: 99%
“…It becomes of great importance to do extensive studies in order to determine if some EOs could be used to treat some bacterial infections or used as disinfectants in clinical environments. Eucalyptus species are some of the plants most described as efficient in antibacterial treatments of some infections such as those of the upper respiratory tract infections (Ben-Arye et al, 2011). Another main concern in modern medicine is drugresistant bacteria and its exponential growth, so the main objective of this assay is to find some compounds that can be used in complementary medicine or as powerful disinfectants against pathogenic bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Eucalyptus has been the topic of several studies due to its extensive applications in traditional medicine, mainly in respiratory infections, proving the efficacy of its' products against upper respiratory tract infections (Ben-Arye et al, 2011). Globulol found in Eucalyptus EOs showed a relevant antimicrobial effect (Manliang et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Main active compound: 1,8-cineole (Nerio et al, 2009;Vilela et al, 2009) 9.10.2. Properties: Anticatarrhale, expectorant and mucolytic, antimicrobial, Antiviral (Ben-Arye et al, 2011;Ben Hadj et al, 2011;Caballero-Gallardo et al, 2011;Gende et al, 2010).…”
Section: Eucalyptus Essential Oil (Eucalyptus Globulus)mentioning
confidence: 99%